Ce-MOF infused membranes with enhanced molecular sieving in the application of dye rejection. Issue 4 (7th March 2023) - Nellur, Usha; Naik, Nagaraj S.; Rego, Richelle M.; Kigga, Madhuprasad; Arthanareeswaran, G.; Padaki, Mahesh
Abstract : An affordable typical nuclide, cerium, found as one of the radioactive wastes, has been employed to prepare MOFs as a practice of recycling and reuse. Further, Ce-based MOF-infused membranes were developed for high-efficiency molecular separation. Abstract : Metal–organic frameworks (MOFs) have been recognized for their promising adsorption-based remedies in decontaminating water sources, but regeneration of spent adsorbent remains a concern. Herein, we developed size- and charge-selective MOF-infused polymeric (PSf) membranes for continuous dye removal based on size and the Donnan exclusion theory. Ce-UiO-66 MOF was synthesized and infused into the PSf matrix to impart hydrophilicity and surface charge. This led to the observation of inherited enhanced flux with improved rejection efficiency. The as-synthesized membranes demonstrated size-selective dye separation among methylene blue (MB), methyl orange (MO), Eriochrome Black T (EBT), rhodamine B (RB), alcian blue (AB), neutral red (NR), and alizarin (AZ) irrespective of charge and intermolecular interactions thereof. The intact MOF infused in the PSf matrix acted upon the improvement of membrane performance such as pure water flux reaching 39.21 L m −2 h −1 with rejection efficiency ∼98% for both MB and AB and ∼99% for EBT. The current work discusses the rational design of modern MOF–PSf membranes with polychronicity in hydrophilicity, porosity and flux, making them out of the ordinary tools for dye rejection. Therefore, this new membrane finds application in size- and charge-selective dye removal.